2015
DOI: 10.1039/c5cp00750j
|View full text |Cite
|
Sign up to set email alerts
|

Functional carbon nanotubes for high-quality charge transfer and moisture regulation through membranes: structural and functional insights

Abstract: Functional single walled carbon nanotubes (SWCNTs) are assembled onto porous supports by using layer-by-layer (LBL) approaches. Directed nano-assembly of nanotubes is identified as a crucial factor for controlling the combined functions of hybrid-composite membranes, including charge and moisture transport. In both the cases, donor-acceptor interactions are indicated to be responsible for the rearrangement of nanotubes inside the LBL multilayer and their related properties. Aggregation and stratification of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…To ensure the build up of a uniform and homogeneous multilayer, SEM images of the film deposited onto the porous substrate ( Fig. [30][31][32] Indeed, the increase in the G/D band intensity ratio reveals a higher aggregate level in solution, while a lower cluster formation is detected for particle power and solid film (Fig. Indeed, the picture revealed the formation of a uniform and very tiny film onto the porous microarray.…”
Section: Resultsmentioning
confidence: 99%
“…To ensure the build up of a uniform and homogeneous multilayer, SEM images of the film deposited onto the porous substrate ( Fig. [30][31][32] Indeed, the increase in the G/D band intensity ratio reveals a higher aggregate level in solution, while a lower cluster formation is detected for particle power and solid film (Fig. Indeed, the picture revealed the formation of a uniform and very tiny film onto the porous microarray.…”
Section: Resultsmentioning
confidence: 99%
“…42,43 Recently it has been shown that functionalized CNTs can be good candidates for efficient charge transfer when incorporated into membranes. 44 It is quite logical that the functionalized nanotubes incorporated into membranes would have conductivities that would be better than those of the matrix. The values of the conductivities are given in Table VIII.…”
Section: Conductivity Measurementsmentioning
confidence: 99%
“…Precisely, titanium oxide (TiO 2 ) nanoparticles (NPs) have been dispersed in polyacrylic acid (PAA) and patterned with poly (diallyldimethyl ammonium chloride) (PDDA) in a hybrid complex that is deposited onto the shell side of polyethylene (PE) hollow-fiber membranes via layer-by-layer (LBL) approach [ 20 , 21 , 22 ]. Commercial PE membranes, which are considered tricky to manage wastewater due to the very high susceptibility to fouling, have been chosen with the intent to demonstrate the real efficiency of the photoactive gel under specific working conditions.…”
Section: Introductionmentioning
confidence: 99%